Zeolite adsorbents for high yield separation of xylenes

By using an octadectic zeolite X-type zeolite adsorbent with controlled Si/Al molar ratio, combined with barium and potassium exchange, a coalescing zeolite adsorbent is formed, which solves the problems of high costs and wastewater discharge in the prior art, and achieves efficient paraxylene separation, improving mechanical strength and selectivity.

CN120435345APending Publication Date: 2025-08-05IFP ENERGIES NOUVELLES +1
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202380087712.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-20
Filing Date
2023-12-19
Publication Date
2025-08-05

AI Technical Summary

Technical Problem

The existing zeolite adsorbents have high synthesis costs when separating paraxylene, serious wastewater discharge problems, and are difficult to use on industrial scale, making it difficult to achieve efficient selective separation of paraxylene.

Method used

An octagonal zeolite X-type zeolite adsorbent with a controlled Si/Al molar ratio is used to form a coalescing zeolite adsorbent through barium and potassium exchange. Combined with a simulated cohesion or countercurrent simulation of simulated moving bed method, efficient separation of paraxylene is achieved.

Benefits of technology

High yield and high purity paraxylene separation is achieved, reducing synthesis costs, reducing wastewater discharge, and improving mechanical strength and selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to coalescent zeolite adsorbents based on faujasite X zeolite crystals, which have a controlled Si / Al molar ratio and exchange with barium; or a coalescent zeolite adsorbent based on faujasite type X zeolite, said zeolite crystals having a controlled Si / Al molar ratio and exchanged with barium and potassium. The invention also relates to the use of the adsorbent in the separation of sugars, polyols, substituted toluene isomers, cresol or the recovery of very high purity paraxylene; the invention also relates to a method for separating xylenes by using the adsorbent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to agglomerated zeolitic adsorbents based on faujasite (FAU) type zeolite crystals having a controlled Si / Al molar ratio, exchanged with barium or with barium and potassium, and exhibiting selective behavior towards para-xylene present in a feed mixture of aromatic hydrocarbons to be separated, the aromatic hydrocarbons including the (C8) isomer containing 8 carbon atoms. Background Art

[0002] It is known in the prior art to use zeolitic adsorbents consisting of faujasite zeolites (FAU) of type X or Y for the selective adsorption of para-xylene in aromatic hydrocarbon mixtures. In addition to sodium cations, the faujasite zeolites of type X or Y contain barium ions and / or potassium ions and / or strontium ions, either alone or in a mixture.

[0003] Patents US3558730, US3558732, US3626020 and US3663638 show that aluminosilicate-based zeolite adsorbents containing sodium and barium (US3960774) or sodium, barium and potassium can effectively separate paraxylene present in a C8 aromatic fraction (a fraction containing aromatic hydrocarbons having 8 carbon atoms).

[0004] For example, patent US Pat. No. 3,878,127 describes a method for preparing these adsorbents, which comprises treating an agglomerate comprising zeolite X and a binder having a Na2O / Al2O3 ratio strictly less than 0.7 in hot sodium hydroxide (soda) in order to replace the exchangeable cations of the zeolite (such as protons or Group IIA cations) with sodium before exchanging with barium or barium and potassium, the prior exchange with sodium making it possible to incorporate a greater amount of barium ions or barium and potassium ions into the zeolite structure.

[0005] These adsorbents are used as adsorbents in liquid phase processes (preferably of simulated countercurrent type, similar to those described in patent US 2 985 589), these adsorbents being particularly applicable to C8 fractions (fractions containing aromatics having 8 carbon atoms).

[0006] The zeolites used in the prior art for separating xylenes are of the faujasite structure type, originally described in patents US2882244 and US3130007, which are crystalline aluminosilicates with cages of well-defined dimensions connected in three dimensions.

[0007] US Patent No. 6,884,918 proposes faujasite X with a Si / Al atomic ratio between 1.15 and 1.5. US Patent No. 6,410,815 teaches a zeolite adsorbent similar to that described in the prior art, but wherein the faujasite has a low silica content and a Si / Al atomic ratio close to 1 (the latter is referred to as LSX, short for Low Silica X, or in French: zéolithe X à faible teneur en silice), which is advantageously used for the separation of para-xylene.

[0008] Therefore, while both zeolite X and low-silicon X zeolite exhibit good paraxylene selectivity, the synthesis of low-silicon X zeolite is considerably more difficult than that of zeolite X. In fact, lowering the Si / Al atomic ratio of faujasite-type zeolite requires increasing the soda consumption used in the zeolite synthesis process. Furthermore, to achieve crystallization at a Si / Al atomic ratio of 1, consistent with the faujasite structure type, high concentrations of potassium hydroxide (potash) must be added to suppress the formation of zeolite A and yield only low-silicon X zeolite. These high levels of sodium and potassium hydroxide consumption increase the manufacturing cost of this zeolite and create issues with wastewater discharge.

[0009] In the references listed above, the zeolite adsorbents are in the form of crystals or agglomerates consisting essentially of zeolite and an inert agglomerated binder, usually in a proportion between 0.1% and 20% by weight.

[0010] Since the synthesis of zeolite X and low-silica X zeolites is usually carried out by nucleation and crystallization of aluminosilicate gels, the resulting crystals are particularly difficult to use on an industrial scale (significant losses of the feed mixture during processing), whereas it is preferred to obtain agglomerated forms (e.g. in the form of granules or grains) which do not suffer from the disadvantages inherent in pulverulent (powdered) materials.

[0011] These agglomerates are prepared, for example, by slurrying (impaste) zeolite crystals with a binder (most commonly a clay or a mixture of clays, possibly a zeolitizable clay) in a ratio of about 80% to 99.9% by weight zeolite crystals to 0.1% to 20% by weight binder. These are then processed into granules, crystallites, beads, pellets or extrudates and heat treated at high temperatures to burn the clay and reactivate the zeolite. Barium and / or potassium exchange may be performed before and / or after the powdered zeolite is agglomerated with the binder.

[0012] The zeolite agglomerates obtained generally have a particle size of a few millimeters and, if the binder and the granulation are chosen according to the rules of the prior art, exhibit a satisfactory set of properties, in particular porosity, mechanical strength and attrition resistance.

[0013] French patent FR2925366 describes a method for producing agglomerates based on LSX zeolite crystals, the agglomerates having a number average diameter less than or equal to 4 µm and a Si / Al atomic ratio of (1.00±0.05)≤Si / Al≤1.15, preferably Si / Al atomic ratio = 1.00±0.05, wherein at least 90% of the exchangeable cation sites are occupied by barium ions alone or by barium ions and potassium ions, wherein the mechanical strength measured by the Shell method series SMS1471-74 applicable to agglomerates with a size less than 1.6 mm is greater than or equal to 2 MPa.

[0014] French patent FR2925367 describes a method for producing an agglomerated zeolite adsorbent, which comprises a mixture of zeolite X crystals, LSX zeolite crystals, and a binder, wherein at least 90% of the zeolite X crystals are exchanged with barium ions alone or with barium and potassium ions, and the exchangeable sites occupied by potassium may account for up to one-third of the exchangeable sites occupied by barium and potassium ions (any possible remainder is generally composed of alkali metal ions or alkaline earth metal ions other than barium and potassium); at least 90% of the LSX zeolite crystals are exchanged with barium ions alone or with barium and potassium ions, and the exchangeable sites occupied by potassium may account for up to one-third of the exchangeable sites occupied by barium and potassium ions (any possible remainder is generally composed of alkali metal ions or alkaline earth metal ions other than barium and potassium); and the proportion of the binder is less than or equal to 20% by weight of the total mass of the agglomerate.

[0015] Patent US6410815 teaches that the performance level of an industrial separation process for separating paraxylene depends largely on: the adsorbent, its adsorption capacity and the degree of selectivity for paraxylene in a medium composed of C8 aromatic compounds (typically paraxylene, metaxylene, o-xylene, ethylbenzene); on the other hand, it depends on the desorption capacity of desorbents such as toluene and para-diethylbenzene for the adsorbed paraxylene. The selectivity of the adsorbent for component A relative to compound B is α A / B It is defined as the ratio of the concentration of the compound in the adsorbed phase divided by the concentration of the compound in the non-adsorbed phase at equilibrium:

[0016] α A / B = A ads / B ads x B liq / A liq

[0017] Among them A ads and B ads are the concentrations of compound A and compound B in the adsorption phase, A liq and B liq are the concentrations of compound A and compound B in the fluid phase. Summary of the Invention

[0018] Surprisingly, it appears that agglomerated zeolitic adsorbents comprising a faujasite-type zeolite (known as MSX, short for Medium Silica X or, in French, zéolithe X à teneurmoyenne en silice) having a controlled Si / Al molar ratio of Si / Al, in particular a Si / Al molar ratio of 1.10≤Si / Al≤1.18, preferably 1.10≤Si / Al≤1.17, even more preferably 1.10≤Si / Al≤1.16, even more preferably 1.11≤Si / Al≤1.16, at least 90% of which is exchanged with barium ions alone or with barium and potassium ions, can advantageously replace the zeolitic adsorbents based on zeolite X and / or based on LSX zeolite, either exchanged with barium or with barium and potassium, described in the literature, alone or in the form of a mixture. The agglomerated zeolitic adsorbents of the present invention show unexpected performance levels in particular in terms of selectivity in para-xylene separation processes. For obvious reasons of ease of implementation and industrial development, the agglomerated zeolitic adsorbents that can be used in the context of the process of the present invention are used alone, preferably without any other zeolitic adsorbents, either in layered form or in the form of a mixture.

[0019] The present invention relates to an agglomerated zeolite adsorbent based on MSX zeolite crystals having a Si / Al atomic ratio of 1.10≤Si / Al≤1.18, preferably 1.10≤Si / Al≤1.17, more preferably 1.10≤Si / Al≤1.16, and even more preferably 1.11≤Si / Al≤1.16, wherein at least 90%, preferably at least 95%, of the exchangeable cation sites are occupied by barium ions alone or by barium and potassium ions. More preferably, the present invention relates to an agglomerated zeolite adsorbent based on MSX zeolite crystals having a Si / Al atomic ratio of 1.11≤Si / Al<1.15, more preferably 1.12≤Si / Al<1.15, and advantageously 1.12≤Si / Al≤1.14, wherein at least 90%, preferably at least 95% of the exchangeable cation sites are occupied by barium ions alone or by barium and potassium ions. Even more preferably, the present invention relates to an agglomerated zeolitic adsorbent based on MSX zeolite crystals having a Si / Al atomic ratio of 1.11 ≤ Si / Al < 1.15, and even more preferably 1.12 ≤ Si / Al < 1.15, and advantageously 1.12 ≤ Si / Al ≤ 1.14, wherein at least 90%, preferably at least 95%, of the exchangeable cation sites are occupied by barium ions alone or by barium and potassium ions.

[0020] The micropore volume of the adsorbent measured by nitrogen adsorption at 77 K according to the Dubinin method after pretreatment at 500 °C for 12 h under vacuum can be greater than or equal to 0.200 cm 3 / g, preferably greater than or equal to 0.220 cm 3 / g, even more preferably greater than or equal to 0.225 cm 3 / g, in an even more preferred embodiment, greater than or equal to 0.250 cm 3 / g.

[0021] The exchangeable sites occupied by potassium may account for up to 1 / 3 of the exchangeable sites occupied by barium + potassium ions, with any possible remainder typically consisting of alkali metal ions or alkaline earth metal ions other than barium and potassium.

[0022] The adsorbent may comprise an inert binder in a proportion less than or equal to 20% by weight, preferably 15% by weight, of the total mass of the adsorbent.

[0023] The adsorbent may have a size distribution such that the number average diameter is from 0.4 mm to 2.0 mm, preferably from 0.4 mm to 0.8 mm.

[0024] The mechanical strength of the adsorbent, measured by the shell method series SMS 1471-74 applicable to agglomerates with a size of less than 1.6 mm, is advantageously greater than or equal to 2 MPa, preferably greater than or equal to 2.5 MPa.

[0025] The loss on ignition, measured at 900° C., is advantageously less than or equal to 7.7%, preferably between 0% and 7.7%, in a preferred manner between 3.0% and 7.7%, in an even more preferred manner between 3.5% and 6.5%, and advantageously between 4.5% and 6.0%, the end points included.

[0026] The number average diameter of the MSX zeolite crystals may be between 0.01 μm and 5 μm, preferably between 0.05 μm and 5 μm, in a very preferred manner between 0.1 μm and 4 μm, in an even more preferred manner between 0.1 μm and 3 μm, in an even more preferred manner between 0.1 μm and 2 μm.

[0027] The invention also relates to a separation process for separating sugars, polyols, substituted toluene isomers, cresols or recovering p-xylene in the liquid or gas phase with the aid of an agglomerated zeolitic adsorbent according to any of the described variants in the presence of a desorbent.

[0028] The method may be a paraxylene recovery method for recovering paraxylene from a C8 aromatic isomer fraction by adsorbing paraxylene with the aid of the agglomerated zeolite adsorbent in the presence of a desorbent in a liquid phase or in a gas phase.

[0029] The recovery process for recovering paraxylene can be carried out by a simulated moving bed process of the simulated co-current or simulated counter-current type.

[0030] The method may be a production method for producing high-purity and high-yield p-xylene from a feed mixture containing aromatic hydrocarbons containing 8 carbon atoms (C8) isomers, the method comprising the steps of:

[0031] a) a contacting step for contacting the feed mixture with a bed of agglomerated zeolite adsorbent in a manner that preferentially adsorbs paraxylene;

[0032] b) a contacting step under desorption conditions for contacting the adsorbent bed with a desorbent, preferably toluene or p-diethylbenzene;

[0033] c) a discharge step for discharging a stream comprising a selectively least adsorbed product of the desorbent and feed mixture from the adsorbent bed;

[0034] d) a discharge step for discharging a stream comprising desorbent and paraxylene from the adsorbent bed;

[0035] e) a separation step for separating the stream obtained from step c) into a first stream comprising the desorbent and a second stream comprising the selectively minimum adsorbed product of the feed mixture; and

[0036] f) a separation step for separating the stream obtained from step d) into a first stream containing the desorbent and a second stream containing para-xylene with a purity level greater than or equal to 75%.

[0037] The method may further comprise the following steps:

[0038] g) a crystallization step in a crystallizer consisting of crystallizing the paraxylene obtained in step f) so as to obtain, on the one hand, paraxylene crystals immersed in its mother liquor and, on the other hand, to obtain part or even all of the mother liquor to be recycled as a mixture with the fresh feed mixture at the inlet of the simulated moving bed adsorption unit; and

[0039] h) a washing step for washing the crystals obtained from step g), at the end of which p-xylene is recovered with a purity of at least 99.7% and preferably at least 99.8%.

[0040] More generally, the present invention finally relates to the use of an agglomerated zeolitic adsorbent based on MSX zeolite crystals having a Si / Al atomic ratio of 1.10≤Si / Al≤1.18, preferably 1.10≤Si / Al≤1.17, even more preferably 1.10≤Si / Al≤1.16, even more preferably 1.11≤Si / Al≤1.16, wherein at least 90% of the exchangeable cationic sites are occupied by barium ions alone or by barium and potassium ions, in the presence of a desorbent, preferably toluene or p-diethylbenzene, for the separation of sugars, polyols, substituted toluene isomers, cresols or the recovery of p-xylene in the liquid or gas phase.

[0041] This use also relates to the recovery of paraxylene from a fraction of C8 aromatic isomers by adsorbing paraxylene in a simulated moving bed reactor of the simulated co-current or simulated counter-current type. DETAILED DESCRIPTION

[0042] The object of the present invention relates to zeolitic adsorbents which can be used in particular for the separation of p-xylene from a mixture of C8 aromatic compounds, these zeolitic adsorbents exhibiting excellent performance levels, in particular in terms of selectivity for p-xylene, said adsorbents being particularly suitable for use in a separation process for the separation of p-xylene in the liquid phase, and most particularly suitable for use in a high-yield separation process for the separation of p-xylene in the liquid phase, preferably of the simulated countercurrent type.

[0043] The agglomerated zeolite adsorbent of the present invention comprises an MSX zeolite having a Si / Al atomic ratio of 1.10≤Si / Al≤1.18, preferably 1.10≤Si / Al≤1.17, even more preferably 1.10≤Si / Al≤1.16, even more preferably 1.11≤Si / Al≤1.16, wherein the lower value reflects the analytical uncertainty in the measurement of this ratio and the higher value reflects the tolerance for product purity regardless of the same analytical uncertainty, at least 90% of the MSX zeolite is exchanged with barium ions alone or with barium ions and potassium ions, and the exchangeable sites occupied by potassium may account for up to 1 / 3 of the exchangeable sites occupied by barium ions plus potassium ions (any possible remainder is generally composed of alkali metal ions or alkaline earth metal ions other than barium and potassium); the mechanical strength of the agglomerated zeolite adsorbent of the present invention is measured by the shell method series SMS1471-74 applicable to agglomerates with a size of less than 1.6 mm and is advantageously greater than or equal to 2 MPa.

[0044] Advantageously, the zeolitic adsorbent of the present invention may include a binder in a proportion less than or equal to 20% by weight, preferably 15% by weight, of the total mass of the agglomerate. This binder may contain one or more zeolitizable clays, and preferably at least 80% by weight of zeolitizable clays, and optionally one or more additives.

[0045] The number average diameter of the zeolite crystals in the zeolite adsorbent of the present invention is advantageously between 0.01 μm and 5 μm, preferably between 0.05 μm and 5 μm, highly preferably between 0.1 μm and 4 μm, even more preferably between 0.1 μm and 3 μm, and even more preferably between 0.1 μm and 2 μm.

[0046] Generally speaking, the zeolite adsorbent of the present invention has a volume average diameter of 0.4 mm to 2 mm, in particular 0.4 mm to 0.8 mm.

[0047] In this document, the term "number-average diameter" or indeed "size" is used for both zeolite crystals and for zeolite agglomerates. The accuracy of the measurement is about 3%.

[0048] The present invention also relates to a method for preparing the zeolite adsorbent of the present invention. The agglomerated zeolite adsorbent of the present invention can be prepared according to the preparation method comprising the following steps:

[0049] a / agglomerating zeolite MSX crystals with a binder containing at least 80% by weight of zeolitizable clay and optional additives, followed by shaping, drying and calcining; and

[0050] -b / If possible, zeolizing the binder by the action of an alkaline solution;

[0051] -c / replacing at least 90% of the exchangeable sites of the MSX zeolite with barium, followed by washing and drying the product thus treated;

[0052] -d / if possible, replacing up to 33% of the exchangeable sites of zeolite X with potassium, and then washing and drying the product thus treated,

[0053] -e / activate.

[0054] Agglomeration and shaping (step a / ) can be carried out according to any technique known to a person skilled in the art, such as extrusion, pressing and agglomeration. The agglomerated binder represents a proportion less than or equal to 20% by weight, preferably 15% by weight, of the total mass of the agglomerate.

[0055] According to a preferred embodiment, the diameter of the zeolite MSX crystals is less than or equal to 5 μm, in a preferred manner between 0.01 μm and 5 μm, preferably between 0.05 μm and 5 μm, in a highly preferred manner between 0.1 μm and 4 μm, in an even more preferred manner between 0.1 μm and 3 μm, and in an even more preferred manner between 0.1 μm and 2 μm.

[0056] At the end of step a / , the finest agglomerate particles can be removed by cycloning and / or sieving, and / or oversized particles can be removed by sieving or crushing, for example in the case of extrudates.

[0057] The agglomerated binder used in step a / comprises at least 80% by weight of a zeolitizable clay and may also contain other mineral binders such as bentonite or attapulgite. The term "zeolitizable clay" is used to refer to a clay or clay mixture that can be converted into a zeolitic material by the action of an alkali / alkaline solution. Zeolitizable clays typically belong to the family of kaolin, kaolinite, nacrite, dickite, halloysite, and / or metakaolin. Kaolin is a commonly used clay.

[0058] During step a / , in addition to the zeolite MSX crystals and the binder, one or more additives may be used (for example additives intended to promote agglomeration or to enhance the hardening of the agglomerates formed).

[0059] Possible additives used in step a) may include any type of silica source known to those skilled in the art specialized in zeolite synthesis, such as colloidal silica, diatomaceous earth, perlite, calcined ash (ie fly ash), sand or any other form of solid silica.

[0060] The zeolite MSX crystals used in the implementation of step a / may originate from a synthesis of sodium-exchanged zeolite MSX crystals, but it does not depart from the scope of the invention to use crystals that have undergone one or more cation exchanges between their synthesis in the NaMSX form and their implementation in step a / .

[0061] The calcination after drying is generally carried out at a temperature of 500 to 600° C. According to a preferred embodiment, step b / of zeolitization is carried out.

[0062] When the zeolitization step b / is performed, at least 50% of the inert, zeolitizable binder is converted into a zeolitic material; it should be noted that the purpose of zeolitization is, in particular, to increase the mechanical strength of the agglomerated zeolitic adsorbent. Zeolitization can be performed by immersing the agglomerated mass in an alkaline / basic solution, typically aqueous, such as an aqueous solution of sodium hydroxide and / or potassium hydroxide, preferably at a concentration greater than 0.5 M. Preferably, this process is performed at elevated temperatures (above ambient temperature), typically between 80°C and 100°C, to enhance process kinetics and reduce the immersion time to less than 8 hours; however, operation at lower temperatures and for longer immersion times does not depart from the scope of the present invention. According to this method of operation, zeolitization (i.e., conversion of the adsorbent-inert binder into the adsorbent-active material) of at least 50% by weight of the binder can be readily achieved. The material is then washed with water before subsequent drying.

[0063] Step c / of exchanging the zeolite cations with barium is carried out by contacting the aggregates obtained from step b / (or d / ) with a barium salt (e.g., BaCl2) in aqueous solution at a temperature between ambient temperature and 100°C, and preferably between 80°C and 100°C. In order to quickly achieve a high degree of barium exchange, i.e., greater than 90%, it is preferred to operate with an excess of barium relative to the zeolite cations required for exchange, generally resulting in a BaO / Al2O3 ratio of about 10 to 12, and to carry out the exchange continuously in such a way as to achieve a target minimum exchange level of at least 90%, preferably at least 95%. Throughout this text, exchange levels are calculated in equivalents rather than in molar concentrations.

[0064] The optional exchange with potassium (step d / ) can be carried out before and / or after the exchange with barium (step c / ), and / or simultaneously using solutions containing barium and potassium ions. As described above, it is also possible to agglomerate zeolite MSX crystals that already contain potassium ions in step a / (by pre-exchanging the NaMSX zeolite with potassium ions before step a / ) and to omit (or not omit) step d / .

[0065] The purpose of activation (step e / ), the final step in the process for obtaining the adsorbent of the invention, is to fix the water content and the loss on ignition of the adsorbent within optimal limits. This is usually done by thermal activation, preferably at a temperature between 200° C. and 300° C. for a period of time, depending on the desired water content and the desired loss on ignition, typically between 1 and 6 hours.

[0066] In one embodiment of the present invention, the agglomerated zeolitic adsorbent of the present invention has a loss on ignition, measured at 900°C according to French standard NF EN 196-2, less than or equal to 7.7%, preferably between 0 and 7.7%, in a preferred manner between 3.0% and 7.7%, in an even more preferred manner between 3.5% and 6.5%, and advantageously between 4.5% and 6.0%, both inclusive.

[0067] The agglomerates obtained from step e / , whether in the form of beads or extrudates, generally have a number-average diameter of 0.4 mm to 2.0 mm, in particular 0.4 mm to 0.8 mm.

[0068] In a general manner, the number average diameter of the zeolite crystals in these zeolitic adsorbents obtained by steps a / to e / is between 0.01 µm and 5 µm, preferably between 0.05 µm and 5 µm, in a highly preferred manner between 0.1 µm and 4 µm, in an even more preferred manner between 0.1 µm and 3 µm, in an even more preferred manner between 0.1 µm and 2 µm.

[0069] The present invention also relates to the use of at least one zeolitic adsorbent according to any of the variants as an adsorbent, which can advantageously replace the adsorbents based on zeolite X or zeolite LSX, exchanged with barium or with barium and potassium, described in the literature, in particular for the following uses:

[0070] - Separation of C8 aromatic isomers (especially xylenes);

[0071] -Separation of sugars;

[0072] - separation of polyols;

[0073] - Separation of substituted toluene isomers (such as nitrotoluene, diethyltoluene, toluenediamine),

[0074] - Separation of cresol;

[0075] -Separation of dichlorobenzene.

[0076] The present invention particularly relates to a method for recovering paraxylene from a C8 aromatic isomer fraction, which comprises using the zeolite adsorbent of the present invention as an adsorbent for adsorbing paraxylene, and the zeolite adsorbent is used not only in liquid phase processes but also in gas phase processes.

[0077] The present invention particularly relates to a process for producing high-purity and high-yield paraxylene from a feed mixture containing aromatic hydrocarbons having 8 carbon atoms (C8) isomers, the process comprising the following steps:

[0078] a) a contacting step under suitable adsorption conditions for contacting the feed mixture with the adsorbent bed of the present invention in a manner that preferentially adsorbs paraxylene;

[0079] b) a contacting step under desorption conditions for contacting the adsorbent bed with a desorbent, preferably toluene or p-diethylbenzene;

[0080] c) a discharge step for discharging a stream comprising a selectively least adsorbed product of the desorbent and feed mixture from the adsorbent bed;

[0081] d) a discharge step for discharging a stream comprising desorbent and paraxylene from the adsorbent bed;

[0082] e) a separation step for separating the stream obtained from step c) into a first stream comprising the desorbent and a second stream comprising the selectively minimum adsorbed product of the feed mixture; and

[0083] f) a separation step for separating the stream obtained from step d) into a first stream containing the desorbent and a second stream containing para-xylene having a purity level greater than or equal to 75%, preferably greater than or equal to 99.7%.

[0084] The method may optionally further comprise the following steps:

[0085] g) a crystallization step in a crystallizer consisting of crystallizing the paraxylene obtained in step f) so as to obtain, on the one hand, paraxylene crystals immersed in its mother liquor and, on the other hand, a mother liquor, part of which or even all of which can be recycled at the inlet of the simulated moving bed adsorption unit as a mixture with the fresh feed mixture; and

[0086] h) a washing step for washing the crystals obtained from step g), at the end of which p-xylene is recovered with a purity of at least 99.7% and preferably at least 99.8%.

[0087] Thus, the desired product can be isolated by preparative adsorptive liquid chromatography (in "batch" mode), advantageously by simulated moving bed liquid chromatography, ie of the simulated countercurrent or simulated cocurrent type, and more particularly of the simulated countercurrent type.

[0088] Chromatographic separations based on simulated countercurrent moving bed chromatography are known in the art. Typically, a simulated moving bed separation unit comprises at least one adsorption column containing multiple adsorbent beds interconnected in a closed loop. The simulated moving bed separation unit includes at least three (and possibly four or five) chromatographic zones, each of which consists of at least one bed or a portion of a column and is located between two consecutive feed or discharge points.

[0089] Typically, at least one feed mixture to be fractionated and a desorbent (sometimes called an eluent) are fed in, and at least one raffinate and an extract are withdrawn. The feed and discharge points vary with time, typically moving toward the bottom of the bed in a synchronized manner.

[0090] By definition, each operating area is represented by a number:

[0091] •Zone 1 = desorption zone for the desired product (contained in the extract), between injection of the desorbent and extraction of the extract;

[0092] • Zone 2 = desorption zone of the raffinate compounds, included between the discharge of the extract and the injection of the feed mixture to be fractionated;

[0093] • Zone 3 = the adsorption zone for the desired product, between the injection of the feed mixture and the removal of the raffinate; and

[0094] • Zone 4, between the removal of the residual liquid and the injection of the desorbent.

[0095] The operating conditions for an industrial adsorption unit of the simulated countercurrent type are typically as follows:

[0096] Number of beds: 6 to 30

[0097] ●Number of zones: at least 4

[0098] Temperature: 100°C to 250°C, preferably 150°C to 190°C

[0099] ● Pressure: between the bubble pressure of xylene and 3 MPa at process temperature;

[0100] The ratio of the desorbent rate to the feed rate is 0.7 to 2.5 (e.g., 0.9 to 1.8 for a single adsorption unit (referred to as a "stand-alone" unit according to generally accepted terminology) and 0.7 to 1.4 for an adsorption unit combined with a crystallization unit);

[0101] • Recycle ratio: 2.5 to 12, preferably 3.5 to 6. The recycle rate is defined as the ratio of the average flow rate through the different adsorbent beds to the flow rate of the feed injected into the adsorbent.

[0102] Further reference may be made to the teachings of US Pat. Nos. 2,985,589, 5,284,992 and 5,629,467.

[0103] The operating conditions of the industrial simulated co-current adsorption unit are substantially the same as those of the simulated counter-current mode, except that the recycle ratio is typically between 0.8 and 7. Further reference may be made to the teachings of US Pat. Nos. 4,402,832 and 4,498,991.

[0104] The desorption solvent may be a desorbent having a lower boiling point than the feed, such as toluene, or a desorbent having a higher boiling point than the feed, such as para-diethylbenzene (PDEB). The adsorbent of the present invention exhibits optimal adsorption selectivity for para-xylene contained in the C8 aromatic fraction when the loss on ignition measured at 900°C is generally less than or equal to 7.7%, preferably between 0 and 7.7%, preferably between 3.0 and 7.7%, more preferably between 3.5 and 6.5%, and advantageously between 4.5 and 6.0% (both inclusive).

[0105] One of the techniques of choice for characterizing the adsorption of molecules from the liquid phase onto porous solids is the breakthrough curve technique. Ruthven, in his book “Principles of Adsorption and Adsorption Processes”, defines the breakthrough curve technique as a way to study the injection of a series of adsorbable species.

[0106] The invention will now be described using the following examples, which are intended to illustrate certain embodiments of the invention and not, however, to limit the scope of the invention as claimed in the appended claims.

[0107] Analytical techniques

[0108] Identification of zeolite phases

[0109] The zeolite MSX in the zeolite adsorbent of the present invention is identified by X-ray diffraction analysis, known to those skilled in the art as DRX. This analysis is performed on a Bruker DRX D8 Advance instrument. Phase identification is performed using Bruker's EVA software and a database containing numerous diffraction patterns known to those skilled in the art (e.g., the database ICCD PDF-2, Issue 2011).

[0110] Si / Al molar ratio and exchange rate

[0111] The Si / Al molar ratio and exchange rate are measured by any analytical chemistry analysis technique known to those skilled in the art.

[0112] Among these techniques, it is worth mentioning the X-ray fluorescence chemical analysis technique using a wavelength dispersive X-ray spectrometer (WDXRF) as described in the French standard NF EN ISO 12677: 2011 (eg Tiger S8 from Bruker).

[0113] X-ray fluorescence (XRF) spectroscopy is a non-destructive spectroscopic analysis technique that uses the photoluminescence of atoms in the X-ray range to determine the elemental composition of a sample. Atoms are typically excited by an X-ray beam or electron bombardment, and once they return to their ground state, a specific radiation is emitted. XRF spectroscopy offers the advantage of being minimally dependent on the chemical composition of the elements, thus enabling precise quantitative and qualitative determinations. In a conventional manner, measurement uncertainties of less than 0.4% by weight are achieved after calibration for each oxide.

[0114] These elemental chemical analyses allow both to verify the Si / Al molar ratio of the initial zeolite and to determine the quality of the ion exchange described in steps c) and optionally d).

[0115] The quality of ion exchange is related to the number of moles of sodium oxide (Na2O) remaining in the agglomerated zeolite adsorbent after exchange. More precisely, the degree of exchange with barium ions is estimated by evaluating the ratio between the number of moles of barium oxide (BaO) and the number of moles of the overall composite (BaO + Na2O). Similarly, the degree of exchange with barium and potassium ions is estimated by evaluating the ratio between the number of moles of barium oxide + potassium oxide (BaO + KO) and the number of moles of the overall composite (BaO + KO + Na2O). It should be noted that the content levels of the various oxides are given as weight percentages relative to the total weight of the anhydrous zeolite adsorbent.

[0116] The Si / Al molar ratio of the zeolite present in the agglomerated zeolite adsorbent was measured by solid-state nuclear magnetic resonance (NMR) spectroscopy of silicon.

[0117] Particle size distribution of zeolite crystals (granulometry):

[0118] The number average diameter of the zeolite crystals and the zeolite crystals contained in the agglomerates used in step a) was estimated by observation using a scanning electron microscope (SEM).

[0119] To estimate the size of the zeolite particles (i.e., crystals) found in the sample, a series of images are taken at a magnification of at least 5,000. The diameters of at least 200 particles are then measured using specialized software, such as Smile View developed by LoGraMi. The measurement accuracy is approximately 3%. A histogram constructed from these diameter measurements also allows the standard deviation σ of the distribution to be determined.

[0120] Observation of zeolite crystals using scanning electron microscopy (SEM) can also be used to distinguish the crystal structures of zeolites (LSX, MSX, X).

[0121] Particle size distribution of zeolite adsorbents (particle size determination):

[0122] The number average diameter of the zeolitic adsorbent obtained as a result of the agglomeration and shaping step a) is determined by analyzing the particle size distribution of the agglomerate sample by imaging the sample in front of a camera lens using a conveyor belt according to ISO 13322-2:2006 standard.

[0123] The number average diameter is then calculated based on the particle size distribution according to ISO 9276-2:2001. In this document, the term "number average diameter" or "size" is used for the zeolite agglomerates. For the size range of the agglomerates of the present invention, the accuracy is about 0.01 mm.

[0124] Micropore volume:

[0125] The crystallinity of the aggregates is also assessed by measuring their micropore volume in comparison with an appropriate reference (a 100% crystalline zeolite under the same cation treatment conditions, or a theoretical zeolite). The micropore volume is determined based on the measurement of the adsorption isotherm of a gas (e.g., nitrogen) at its liquefaction temperature.

[0126] Before adsorption, under vacuum (P<6.7.10 -4 The zeolitic adsorbent was degassed at 300° C. to 450° C. for 9 to 16 hours at a pressure of 1.5 Pa. The nitrogen adsorption isotherm at 77 K was then measured on an ASAP 2020M apparatus from Micromeritics by taking at least 35 measurement points at a relative pressure with a P / P0 ratio between 0.002 and 1.

[0127] Loss on ignition of zeolite adsorbent:

[0128] The loss on ignition is determined by calcining the sample in air at a temperature of 900°C ± 25°C in an oxidizing atmosphere, according to the operating procedure described in French standard NF EN 196-2 (April 2006). The standard deviation of the measurement is less than 0.1%.

[0129] Example

[0130] Example 1: (Comparative): Preparation of a BaLSX-type adsorbent containing a zeolitic binder

[0131] In this example, a prior art adsorbent was produced and tested.

[0132] 840 g (expressed as calcined equivalent) of zeolite LSX crystals with a Si / Al ratio of 1.01 and 160 g (expressed as calcined equivalent) of kaolin were thoroughly mixed and agglomerated with an amount of water sufficient to allow agglomeration by extrusion. The extrudates were dried and then pulverized to recover particles with an equivalent diameter of 0.7 mm. These were then calcined at 550°C for 2 hours under a nitrogen stream.

[0133] 200 g of the particles thus obtained are placed in a glass reactor equipped with a double jacket and the temperature is adjusted to 95±1° C.; 700 mL of a 220 g / L aqueous sodium hydroxide solution are subsequently added and the reaction medium is then left under stirring for 3 hours.

[0134] The particles are then subjected to four successive washing operations with water, followed by emptying the reactor. The effectiveness of the washing is determined by measuring the final pH of the wash water, which should be between 10 and 10.5.

[0135] Barium exchange was then carried out under the same operating conditions as in Example 1, followed by a washing operation, and then drying at 80° C. for 2 hours, and finally followed by activation at 200° C. under a nitrogen flow for 2 hours.

[0136] The degree of barium exchange of the adsorbent was 97%. After pretreatment at 500 ° C for 12 h under vacuum, the micropore volume measured by nitrogen adsorption at 77 K according to the Dubinin method was 0.235 cm 3 / g.

[0137] Mechanical strength was also measured using the method described in the present invention. The pressure required to obtain 0.5% fines was 2.70 MPa.

[0138] Example 2 (Comparative): Preparation of a BaX-type adsorbent containing a zeolitic binder

[0139] In this example, a prior art adsorbent was produced and tested.

[0140] 900 g (expressed as calcined equivalent) of zeolite X crystals having a Si / Al ratio of 1.25 and an average crystal size of 1.6 µm were agglomerated by thoroughly mixing them with 170 g (expressed as calcined equivalent) of kaolin, 70 g of colloidal silica sold under the trade name Klebosol® 30 (containing 30% by weight of SiO2 and 0.5% of Na2O), and the appropriate amount of water required to form agglomerates by extrusion. The extrudates were dried and then comminuted in such a way as to recover agglomerates with an equivalent diameter of 0.7 mm, which were then activated at 550°C for 2 hours under a stream of nitrogen.

[0141] 200 g of the granules thus obtained were placed in a double-jacketed glass reactor and the temperature was adjusted to 100 ± 1°C. 1.5 L of a 100 g / L aqueous sodium hydroxide solution were then added, and the reaction medium was stirred for 3 hours. The granules were then washed three times in succession with water, and the reactor was subsequently emptied. The effectiveness of the washing was determined by measuring the final pH of the wash water, which should be between 10 and 10.5.

[0142] Barium exchange was then carried out under the same operating conditions as in Example 1, followed by a washing operation, and then drying at 80° C. for 2 hours, and finally followed by activation at 200° C. under a nitrogen flow for 2 hours.

[0143] The degree of barium exchange of the adsorbent was 95%.

[0144] After pretreatment at 500 °C for 12 h under vacuum, the micropore volume measured by nitrogen adsorption at 77 K according to the Dubinin method was 0.256 cm 3 / g.

[0145] Mechanical strength was also measured using the method described in the present invention. The pressure required to obtain 0.5% fines was 2.50 MPa.

[0146] Example 3 (comparative): 50:50 weight mixture of samples from Examples 1 and 2 (BaLSX type zeolite adsorbent and BaX type zeolite absorbent)

[0147] The samples of Examples 1 and 2 were mechanically mixed in a 50:50 weight ratio.

[0148] The apparent Si / Al molar ratio of the mixture was 1.13.

[0149] Example 4 (Invention): Preparation of a BaMSX-type adsorbent comprising a zeolitized binder

[0150] According to Table 4 of US Patent No. 6,596,256, Example 27, BaMSX crystals (Si / Al = 1.14) were prepared.

[0151] The zeolite crystal size was analyzed by scanning electron microscopy. The average crystal size was 2.8 µm.

[0152] 840 g (expressed as calcined equivalent) of these zeolite MSX crystals were thoroughly mixed and agglomerated with 170 g (expressed as calcined equivalent) of kaolin, 40 g of colloidal silica sold under the trade name Klebosol® 30 (containing 30% by weight of SiO2 and 0.5% of Na2O), and a suitable amount of water to enable agglomeration by extrusion. The extrudates were dried and then comminuted in such a way as to recover particles having an equivalent diameter of 0.7 mm, which were then calcined at 600°C for 2 hours in a stream of nitrogen.

[0153] 200 g of the granules thus obtained were placed in a double-jacketed glass reactor and the temperature was adjusted to 95 ± 1°C. 700 mL of a 170 g / L aqueous sodium hydroxide solution was then added, and the reaction medium was stirred for 3 hours. The granules were then washed three times with water, and the reactor was then emptied.

[0154] The effectiveness of the wash is determined by measuring the final pH of the wash water, which should be between 10 and 10.5.

[0155] Barium exchange was then carried out under the same operating conditions as in Example 1, followed by a washing operation, and then drying at 80° C. for 2 hours, and finally followed by activation at 200° C. under a nitrogen flow for 2 hours.

[0156] The degree of barium exchange of the adsorbent was 97%. After pretreatment at 500 ° C for 12 h under vacuum, the micropore volume measured by nitrogen adsorption at 77 K according to the Dubinin method was 0.255 cm 3 / g.

[0157] Mechanical strength was also measured using the method described in the present invention. The pressure required to obtain 0.5% fines was 2.60 MPa.

[0158] The agglomerated zeolite adsorbent of BaMSX of the present invention is obtained.

[0159] Example 5: Penetration Test (Frontal Chromatography)

[0160] The Loss On Ignition (LIO) was adjusted to a value of 6.0% for each sample.

[0161] These adsorbents were then subjected to a breakthrough test (head-on chromatography) to determine their effectiveness. The amount of adsorbent used for this test was approximately 82 g.

[0162] The operating method and the composition of the feed were the same as those of Example 1.

[0163] The operation method to obtain the penetration curve is as follows:

[0164] -Fill the column with mesh or sieves and place the column on the test bench.

[0165] -Fill with solvent at ambient temperature.

[0166] - In the solvent flow (5 cm 3 / min), and gradually increase the adsorption temperature.

[0167] -When the adsorption temperature is reached, the 3 / min inject solvent.

[0168] -Solvent / feed displacement to inject feed (10 cm 3 / min).

[0169] - the injection of the feed is then maintained long enough to reach thermodynamic equilibrium; and

[0170] -Collect and analyze the flow-through effluent.

[0171] The pressure was sufficient to keep the feed in the liquid phase, i.e. 1 MPa. The adsorption temperature was 175°C.

[0172] The feed composition is as follows:

[0173] p-Xylene: 45 wt%

[0174] Meta-xylene: 45% by weight

[0175] Isooctane: 10 wt% (used as a tracer to estimate the non-selective volume and does not participate in the separation)

[0176] The penetration results are summarized in Table 1.

[0177] Table 1

[0178]

[0179] (1) PX: paraxylene, MX: metaxylene

[0180] In a surprising manner, the zeolitic adsorbents of the invention have a higher selectivity for p-xylene than for m-xylene, the m-xylene selectivity being much higher than that measured with the zeolitic adsorbents of the prior art.

Claims

1. An agglomerated zeolite adsorbent based on MSX zeolite crystals, wherein the Si / Al atomic ratio is 1.10≤Si / Al≤1.18, preferably 1.10≤Si / Al≤1.17, more preferably 1.10≤Si / Al≤1.16, and more preferably 1.11≤Si / Al≤1.16, wherein: At least 90%, preferably at least 95%, of the exchangeable cationic sites are occupied by barium ions alone or by barium and potassium ions.

2. The agglomerated zeolite adsorbent according to claim 1, wherein After pretreatment at 500 °C for 12 h under vacuum, the micropore volume measured by nitrogen adsorption at 77 K according to the Dubinin method is greater than or equal to 0.200 cm 3 / g, preferably greater than or equal to 0.220 cm 3 / g, even more preferably greater than or equal to 0.225 cm 3 / g, in an even more preferred embodiment greater than or equal to 0.250 cm 3 / g.

3. The agglomerated zeolite adsorbent according to claim 1, wherein The exchangeable sites occupied by potassium account for at most one-third of the exchangeable sites occupied by barium + potassium ions, with any possible remainder typically consisting of alkali metal ions or alkaline earth metal ions other than barium and potassium.

4. The agglomerated zeolite adsorbent according to claim 1, comprising an inert binder in a proportion less than or equal to 20 wt%, preferably 15 wt%, of the total mass of the agglomerate.

5. An agglomerated zeolitic adsorbent according to any one of the preceding claims, having a size distribution such that the number average diameter is from 0.4 mm to 2.0 mm, preferably from 0.4 mm to 0.8 mm.

6. The agglomerated zeolite adsorbent according to any one of the preceding claims, wherein The mechanical strength measured by the shell method series SMS1471-74, applicable to agglomerates with a size of less than 1.6 mm, is greater than or equal to 2 MPa, preferably greater than or equal to 2.5 MPa.

7. The agglomerated zeolite adsorbent according to any one of the preceding claims, wherein The loss on ignition, measured at 900°C, is less than or equal to 7.7%, preferably between 0 and 7.7%, in a preferred manner between 3.0% and 7.7%, in an even more preferred manner between 3.5% and 6.5%, and advantageously between 4.5% and 6.0%, both inclusive.

8. The agglomerated zeolite adsorbent according to any one of the preceding claims, wherein The number average diameter of the MSX zeolite crystals is between 0.01 μm and 5 μm, preferably between 0.05 μm and 5 μm, in a highly preferred manner between 0.1 μm and 4 μm, in an even more preferred manner between 0.1 μm and 3 μm, in an even more preferred manner between 0.1 μm and 2 μm.

9. A separation method for separating sugars, polyols, substituted toluene isomers, cresols or recovering p-xylene in the presence of a desorbent in a liquid phase or a gas phase by using the agglomerated zeolite adsorbent according to any one of claims 1 to 8.

10. The method for recovering p-xylene according to claim 9, which is used for recovering p-xylene from the C8 aromatic isomer fraction by adsorbing p-xylene by the agglomerated zeolite adsorbent in the presence of a desorbent in a liquid phase or in a gas phase.

11. The recovery method according to any one of claims 9 or 10, which is carried out by a simulated moving bed method of a simulated co-current type or a simulated counter-current type.

12. A production process according to any one of claims 9 to 11 for producing high-purity and high-yield paraxylene from a feed mixture comprising aromatic hydrocarbons containing (C8) isomers having 8 carbon atoms, the process comprising the following steps: a) a contacting step for contacting the feed mixture with an agglomerated zeolite adsorbent bed in a manner that preferentially adsorbs p-xylene; b) a contacting step under desorption conditions for contacting the adsorbent bed with a desorbent, preferably toluene or p-diethylbenzene; c) a discharge step for discharging a stream comprising the desorbent and the selectively least adsorbed product of the feed mixture from the adsorbent bed; d) a discharge step for discharging a stream containing the desorbent and paraxylene from the adsorbent bed; e) a separation step for separating the stream obtained from step c) into a first stream containing the desorbent and a second stream containing the selectively minimum adsorbed product of the feed mixture; as well as f) a separation step for separating the stream obtained from step d) into a first stream containing said desorbent and a second stream containing para-xylene having a purity level greater than or equal to 75%.

13. The method of claim 12, further comprising: g) a crystallization step in a crystallizer, consisting in crystallizing the para-xylene obtained in step f) so as to obtain, on the one hand, para-xylene crystals immersed in its mother liquor and, on the other hand, a mother liquor which is partially or even completely recycled at the inlet of the simulated moving bed adsorption unit as a mixture with the fresh feed mixture; as well as h) a washing step for washing the crystals obtained from step g), at the end of which paraxylene is recovered with a purity of at least 99.7% and preferably at least 99.8%.

14. Use of an agglomerated zeolite adsorbent based on MSX zeolite crystals in the presence of a desorbent for separating sugars, polyols, substituted toluene isomers, cresols, or recovering p-xylene in a liquid or gas phase, wherein the MSX zeolite crystals have a Si / Al atomic ratio of 1.10≤Si / Al≤1.18, preferably 1.10≤Si / Al≤1.17, even more preferably 1.10≤Si / Al≤1.16, even more preferably 1.11≤Si / Al≤1.16, wherein: At least 90% of the exchangeable cationic sites are occupied by barium ions alone or by barium ions and potassium ions, and the desorbent is preferably toluene or p-diethylbenzene.

15. Use of the agglomerated zeolite adsorbent according to claim 14 for recovering p-xylene from a C8 aromatic isomer fraction by adsorbing p-xylene in a simulated moving bed reactor of a simulated co-current type or a simulated counter-current type.

Citation Information

Patent Citations

  • AGGLOMERATED ZEOLITIC adsorbents, THEIR PREPARATION PROCESS AND THEIR USES

    FR2925366A1

  • AGLLOMERIC ZEOLITIC adsorbents, THEIR PREPARATION PROCESS AND THEIR USES

    FR2925367A1

  • Molecular sieve adsorbents

    US2882244A

  • Continuous sorption process employing fixed bed of sorbent and moving inlets and outlets

    US2985589A

  • Crystalline zeolite y

    US3130007A